Politics of love: Love as a religious and political discourse in modern China through the lens of political leaders - Guo, Ting (Critical research on religion, 2020)
As part of a larger project, this paper serves as an overview that examines how "ai" ? (love) as an affective concept made its way into the Chinese vocabulary, how it gained popularity at specific junctures in modern Chinese history, and the ways in which it has been adapted as a marker of modernity and a political discourse in Republican (1911-49) and Communist China (1949-) in distinct ways. Although literary scholars have noted the significance of the shaping of love as an affective concept for the project of Chinese modernity, they mainly focus on the conceptions and interpretations of love in the literature, and with a time frame from late imperial (1368-1911) to Maoist China (1949-76). The few studies about love in post-Mao era usually attribute the sources of such affect to Christianity. My paper makes a fresh contribution in three aspects. First, I take a longer historical perspective, from the 1910s to the 2010s, and dedicate, secondly, a large part of my study to the decisive impact from revolutionary radicalism to popular religions on the formation of the discourse of state propaganda and everyday politics, rather than manifestations in the literature and sources from Christianity. Third, I study some of the most controversial political figures in modern China, including Sun Yat-sen (1866-1925), Mao Zedong (1893-1976), and Xi Jinping (1953-), rather than intellectuals and writers only.